Design and 3D printing of miniaturized dialyzers for laboratory use (Transactions on Additive Manufacturing Meets Medicine, 2021)
The limiting factor of extracorporeal blood purification in preclinical testing is the large volume of blood required. For this reason, developing miniaturized devices for few milliliters of patient’s blood is the focus of this work. Clinical dialyzers are adapted to the sample volume by appropriate downscaling. The housings were created digitally, printed using polyjet technology and iteratively refined. A design was achieved that enables optimal potting results and homogeneous distribution of fibers within the dialyzer. Minia-turized housings with complex design and high resolution could be realized. Nevertheless, performance comparison to the clinical device is necessary for future laboratory application.
Keywords: miniaturized dialyzers; extracorporeal blood purification; additive manufacturing; polyjet; design